A Case Report: Alpert's Syndrome with Anterior Lenticonus and Fundus Lesions - Katzman, M.M. (Canadian Journal of Optometry, 2026)
The patient J.S. was first seen in my office with his sister 4/8/79. He was born 12/12/63 making him 16 years of age. A case history was taken and his chief complaint was not seeing clearly in the distance. He had been wearing glasses for approximately two years and his last examination was nine month previous.